Postbiotics: a perspective on their quantification - Vinderola, Gabriel; Benkowski, Andrzej; Bernardeau, Marion; Chenoll, Empar; Collado, Maria Carmen; Cronin, Ultan; Eckhardt, Erik; Green, Justin B.; Ipharraguerre, Ignacio R.; Kemperman, Rober; Lacroix, Christophe; Minami, Junichi; et al. (FRONTIERS MEDIA SA, 2025)
A "postbiotic" is a preparation of inanimate microorganisms and/or their components that confers a health benefit on the host. To encourage collaborative problem-solving to address the issues related to the characterization and quantification of postbiotics, a working group of academic and industry scientists involved in research or commercial production of postbiotics convened at the International Scientific Association for Probiotics and Prebiotics (ISAPP) 2024 meeting. This paper reports the outcomes of that discussion. Postbiotics are potentially compositionally complex mixtures, leading us to anticipate that full characterization and quantification of all components of a postbiotic product is not feasible. However, confirmation of the identity and quantity of the progenitor microorganism(s), quantification of some of its functional components, and a suitable description of the process of inactivation will be needed to assure the product can be sufficiently described and consistently reproduced. Measurement and quantification must be fit for purpose. Some useful methods include flow cytometry (FC), including innovations such as imaging FC, which has evolved into a mainstream technique suited to quantify inanimate cells, and quantitative polymerase chain reaction, which complements FC by enabling quantification and identity of microbes to the strain level. Other methods can be utilized depending on the complexity, type of microorganisms used (bacteria, yeasts, filamentous fungi), number of strains and cell integrity (intact vs. fragmented). Hence, no 'gold standard' methodology - analogous to colony-forming units for probiotics - is envisioned for postbiotics. This perspective focuses on the required microbial composition of postbiotics, not on the optional metabolite components, which can be measured using well-established methods. We propose a decision tree to aid deliberation among different quantification methods for postbiotics under development and being commercialized. We recognize that the evolution of technologies will likely result in future refinement of this decision tree, and we emphasize that our intent is not to prescribe a rigid framework, but rather to provide guiding principles on approaches to quantifying postbiotics.